FEEDING AND BREEDING MANAGEMENT PRACTICES OF SHEEP IN TELANGANA REGION OF ANDHRA PRADESH* (Indian Journal of Animal Production and Management, 2014)
A survey on a study on feeding and breeding management practices adopted by sheep farmers in Telangana region of Andhra Pradesh was carried out with a sample size of 576 farmers across three zones by using multistage stratified random sampling technique. The survey revealed that farmers of these three zones mainly depend on grazing under extensive system to rear their flocks and the mean grazing time (hrs) and distance (km) in summer was 7.80 ± 0.04 and 6.00 ± 0.04 whereas mean grazing time (hrs) and distance other than summer months was 5.29 ± 0.05 and 3.76 ± 0.03, respectively. A Significant (P
Keywords: Sheep; Feeding and breeding practices; Telangana region; Andhra Pradesh